Trace metal distributions in Posidonia oceanica and sediments from Taranto Gulf (Ionian Sea, Southern Italy) - DI LEO, A.; ANNICCHIARICO, C.; CARDELLICCHIO, N.; SPADA, L.; GIANDOMENICO, S. (Mediterranean Marine Science, 2013)
Distribution of metals (Hg, Pb, Sn, Cu, Cd and Zn) was determined in sediments and in different tissues of Posidonia oceanica collected from San Pietro Island, Taranto Gulf (Ionian Sea, Southern Italy). In seagrass, results, compared with metal concentrations in sediments, showed that the highest concentrations of Hg, Pb, Sn and Cu were found in the roots, while in the green leaves were found the highest levels of Cd and Zn. Instead the lowest metal concentrations were found in the basal part of the leaf. Levels of metals in the leaves were similar to those found by other authors in uncontaminated areas of the Mediterranean Sea. Mercury levels in roots were correlated to levels in sediments. This could demonstrate the plant memorizes sediments contamination . This study reinforces the usefulness and the relevance of Posidonia oceanica as an indicator of spatial metal contamination and an interesting tool for environmental quality evaluation.